Reconstruction Policy and Planning - International Recovery Platform; Tanaka, Yasuo; Shiozaki, Yoshimitsu; Hokugo, Akihiko; Bettencourt, Sofia (World Bank, Washington, DC, 2013)
The unprecedented damage caused by the Great East Japan Earthquake (GEJE) affected multiple locations, posing severe challenges for local governments. Based on advice from an independent council, the government acted quickly and issued a basic policy and regulation framework within four months, laying the foundation for an inclusive process of recovery and reconstruction. This note documents the interactive process of reconstruction planning, as conducted by various levels of government with the active engagement of affected people, experts, volunteers, and the private sector. This report gives findings; lessons; and recommendations for developing countries.